Efektifitas Metode Pembelajaran Klinik Terhadap Kemampuan Berpikir Kritis Dan Kepercayaan Diri Mahasiswa Keperawatan : A Literature Review - Patmawati, Try Ayu; Saleh, Ariyanti; Syahrul, Syahrul (Jurnal Keperawatan Muhammadiyah, 2018)
Background : Critical thinking of nursing students have to be increased considering the importance of these things in making decisions, problem solving and clinical judgment and supported by self confidence. Although critical thinking and self confidence are important, but all of students are not able to do that. For this reason, clinical instructor have to make innovation through learning methods to achieve this. The purpose of this literature review is to identify the clinical learning method affecting the critical thinking and self confidence of nursing students.Method:   the data base used in making this review of literature are Pubmed, Science Direct, and Google Scholar published in 2007-2018. Result:  From the 12 articles used in this literature review, it was found that in order to improve the critical thinking and self confidence of nursing students in a clinical environment, the clinical supervisor can use student-centered learning methods and can even involve patients. The learning methods include simulation, nursing round method, demonstration models, clinical conference, and concept mappimg.Conclusion :   the learning method affected the critical thinking and self confidence of nursing students including clinical conference, simulations, demonstration models, concept mapping and nursing rounds. Therefore the supervisor must be able to know and choose what method is appropriate for clinical guidance.